The Effect Of Using Tiktok Application Into Students Speaking Mastery The Tenth Grade At SMK Gelora Jaya Nusantara - Widya Ningsih Simalango; Sahlan Tampubolon (Lembaga Riset dan Inovasi Almatani, 2026)
This research aimed to examine The Effect Of Using The Tiktok Application On The Speaking Mastery Of Tenth-Grade Students At SMK Gelora Jaya Nusantara Medan. The study applied a quantitative research with pre-test and post-test, involving two groups: the experimental group, which learned speaking through TikTok-based media, and the control group, which was taught using conventional methods. A total of 67 students participated in this study. Data were collected through speaking tests that measured vocabulary, pronunciation, grammar, fluency, confidence, and accuracy. The findings showed that the mean score of the experimental group in the post-test was significantly higher than in the pre-test, and also higher compared to the control group. These results indicate that the use of TikTok had a positive and significant impact on students’ speaking mastery. The platform provided opportunities for students to practice creatively and confidently, making the learning process more interactive and enjoyable. Therefore, integrating TikTok as a supplementary learning medium can effectively support the improvement of students’ English-speaking skills.